Asymmetric [4 + 2] cycloaddition synthesis of 4H-chromene derivatives facilitated by group-assisted-purification (GAP) chemistry. Issue 63 (14th December 2021) - Rouh, Hossein; Tang, Yao; Zhang, Sai; Ali, Ahmed I. M.; Surowiec, Kazimierz; Unruh, Daniel; Li, Guigen
Abstract : A new asymmetric method for the synthesis of highly functionalized 4 H -chromenes was developed via Group-Assisted Purification (GAP) chemistry and shown in good to high yield and excellent diastereoselectivity. Abstract : In this work, we present a strategy for the preparation of functionalized 4 H -chromene derivatives via a Cs2 CO3 -catalyzed [4 + 2] cycloaddition of enantiopure chiral salicyl N -phosphonyl imines with allenoates. Fifteen examples were achieved in excellent yields and diastereoselectivity. The products were purified simply by washing the crude mixture with hexanes following the Group-Assisted Purification (GAP) chemistry/technology to bypass traditional separation methods. The absolute configuration was unambiguously determined by X-ray structure analysis.